Etnoconhecimentos sobre animais de pescadores artesanais na Amazônia costeira paraense - SANTOS, Claudia Nunes (Universidade Federal do Pará, 2021)
The fauna diversity, as well as the human diversity, in Amazon has been studied by several specialists in search of understanding the life and evolution of this system. To overcome the limits of interpretations produced, besides using different tools, techniques and approaches from different scientific disciplines, it is necessary to consider the subjectivities pertaining to this complex. Local, traditional, or ethnoknowledge of different peoples and communities broadens the view on the socio-biodiversity. One effort that guide Ethnobiology is the break with a way of do research that separates society and nature, as well as the understanding that knowledge is built in the relationship between people researched and who research. Here, I present some conservationist inferences about interactions between fishermen with sea turtles and coastal birds. The surveys were carried out between 2015 and 2018, in six fishing communities in the municipalities of Bragança, Tracuateua and Salinópolis, in the state of Pará. The rich ethnozoologies and ethnotaxonomies of artisanal fishermen on local sea turtles and coastal birds, reveal a profound knowledge about these animals that are not of self-support or economic interest. Furthermore, fishermen's awareness of the importance of animals to ecosystems is an important ethnoknowledge for understanding human-animal relations, as well as for locally referenced preservation and management actions.